PENGARUH KREDIBILITAS BRAND AMBASSADOR “BANGTAN SONYEONDAN (BTS)” DAN BRAND IMAGE “TOKOPEDIA” TERHADAP MINAT AKSES APLIKASI E-COMMERCE: (Studi Deskriptif Kuantitatif Pada Komunitas BTS Army Amino Bandung) - Novie Susanti S; Annisa Husnusyifa; Novi Hidayati (Commed : Jurnal Komunikasi dan Media, 2022)
This study aims to determine and explain how the influence of the credibility of the Ambassador brand "Bangtan Sonyeondan (BTS)" and Brand Image "Tokopedia" on the interest in accessing e-Commerce applications. In this study, the population of this study is the Army Amino BTS Community Bandung with a sample size of 92 respondents. The sampling technique uses probability sampling with the type of simple random sampling. The approach used by researchers is a quantitative approach to the type of survey research methods. Data collection techniques used were questionnaire and documentation researchers while the data analysis techniques used by researchers were the normality test, multiple linear regression testing, and the coefficient of determination with the help of SPSS software. Based on the results of the research conducted, it shows that the credibility of the Brand Ambassador "Bangtan Sonyeondan (BTS)" and the Brand Image "Tokopedia" has a positive and significant effect on E-Commerce Application Access Interest. The selection of a brand ambassador with an attractive appearance, qualified expertise and high credibility will present the brand image of a product to attract and increase consumer interest and interest in accessing e-commerce applications, especially "Tokopedia".